One step toward Jerusalem : oral histories of Orthodox Jews in Stalinist Hungary - Bacskai, Sándor (Modern Jewish history., 2018)
Originally published in 1997, Bacskai's powerful ethnography portrays the political, religious, and individual forces that came to bear on the Orthodox Jewish tradition as it struggled for survival in the aftermath of the Holocaust in Hungary. Jews who returned to their homes eagerly reestablished their close-knit community lives. However, they were greeted with hostility and faced daily prejudice. Following the fall of Hungarian democracy, the number of Orthodox Jewish congregations dramatically decreased. Those who remained struggled to combat antisemitism and antizionism. It is these individuals, the bearers of the Orthodox Jewish tradition, whom Bacskai celebrates and gives voice to inOne Step toward Jerusalem. Through detailed interviews and intimate profiles, Bacskai narrates the individual stories of survival and the collective story of Jews struggling to maintain a community despite significant resistance.